Future of the Inland Waterway Transport - Cempírek, Václav; Čejka, Jiří (My University, 2017)
The paper is concerned with the inland waterway transport in the Czech Republic, which has been considerably stagnating since the 90´s of the last century. The unfavorable development of the waterway transport has an adverse influence on the development of transport companies, shipbuilding industry and, last but not least, the national economy. In future, the waterway transport can play an important role especially in transporting the energy sources.
Budoucnost vnitrozemské vodní dopravy
Keywords: waterway transport; traffic volume; transport performance; classification of inland waterways; vodní doprava; objem dopravy; výkonnost dopravy; klasifikace vnitrozemských vodních cest